The effects of fiscal policy in an estimated DSGE model: The case of the German stimulus packages during the great recession - Andrej Drygalla; Oliver Holtemöller; Konstantin Kiesel (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2017)
In this paper, we analyse the effects of the stimulus packages adopted by the German government during the Great Recession. We employ a standard mediumscale dynamic stochastic general equilibrium (DSGE) model extended by nonoptimising households and a detailed fiscal sector. In particular, the dynamics of spending and revenue variables are modeled as feedback rules with respect to the cyclical component of output. Based on the estimated rules, fiscal shocks are identified. According to the results, fiscal policy, in particular public consumption, investment, transfers and changes in labour tax rates including social security contributions prevented a sharper and prolonged decline of German output at the beginning of the Great Recession, suggesting a timely response of fiscal policy. The overall effects, however, are small when compared to other domestic and international shocks that contributed to the economic downturn. Our overall findings are not sensitive to the allowance of fiscal foresight.
urn:nbn:de:gbv:3:2-87032
Keywords: C32; E32; E62; 330; fiscal policy shocks; DSGE model; Bayesian inference; stimulus packages